Ibrutinib combined with bendamustine and rituximab compared with placebo, bendamustine, and rituximab for previously treated chronic lymphocytic leukaemia or small lymphocytic lymphoma (HELIOS): a randomised, double-blind, phase 3 study. Issue 2 (February 2016) - Chanan-Khan, Asher; Cramer, Paula; Demirkan, Fatih; Fraser, Graeme; Silva, Rodrigo Santucci; Grosicki, Sebastian; Pristupa, Aleksander; Janssens, Ann; Mayer, Jiri; Bartlett, Nancy L; Dilhuydy, Marie-Sarah; Pylypenko, Halyna; et al.
Summary: Background: Most patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma relapse after initial therapy. Bendamustine plus rituximab is often used in the relapsed or refractory setting. We assessed the efficacy and safety of adding ibrutinib, an oral covalent inhibitor of Bruton's tyrosine kinase (BTK), to bendamustine plus rituximab in patients with previously treated chronic lymphocytic leukaemia or small lymphocytic lymphoma. Methods: The HELIOS trial was an international, double-blind, placebo-controlled, phase 3 study in adult patients (≥18 years of age) who had active chronic lymphocytic leukaemia or small lymphocytic lymphoma with measurable lymph node disease (>1·5 cm) by CT scan, and had relapsed or refractory disease following one or more previous lines of systemic therapy consisting of at least two cycles of a chemotherapy-containing regimen, an Eastern Cooperative Oncology Group (ECOG) performance status of 0–1, and adequate bone marrow, liver, and kidney function. Patients with del(17p) were excluded because of known poor response to bendamustine plus rituximab. Patients who had received previous treatment with ibrutinib or other BTK inhibitors, refractory disease or relapse within 24 months with a previous bendamustine-containing regimen, or haemopoietic stem-cell transplant were also excluded. Patients were randomly assigned (1:1) by a web-based system to receive bendamustine plus rituximab given in cycles of 4 weeks' duration (bendamustine: 70 mg/m 2 intravenously on days 2–3 in cycle 1, and days 1–2 in cycles 2–6; rituximab: 375 mg/m 2 on day 1 of cycle 1, and 500 mg/m 2 on day 1 of cycles 2–6 for a maximum of six cycles) with either ibrutinib (420 mg daily orally) or placebo until disease progression or unacceptable toxicity. Patients were stratified according to whether they were refractory to purine analogues and by number of previous lines of therapy. The primary endpoint was independent review committee (IRC)-assessed progression-free survival. Crossover to ibrutinib was permitted for patients in the placebo group with IRC-confirmed disease progression. Analysis was by intention-to-treat and is continuing for further long-term follow-up. The trial is registered withClinicalTrials.gov, numberNCT01611090 . Findings: Between Sept 19, 2012, and Jan 21, 2014, 578 eligible patients were randomly assigned to ibrutinib or placebo in combination with bendamustine plus rituximab (289 in each group). The primary endpoint was met at the preplanned interim analysis (March 10, 2015). At a median follow-up of 17 months (IQR 13·7–20·7), progression-free survival was significantly improved in the ibrutinib group compared with the placebo group (not reached in the ibrutinib group (95% CI not evaluable) vs 13·3 months (11·3–13·9) in the placebo group (hazard ratio [HR] 0·203, 95% CI 0·150–0·276; p<0·0001). IRC-assessed progression-free survival at 18 months was 79% (95% CI 73–83) in the ibrutinib group and 24% (18–31) in the placebo group (HR 0·203, 95% CI 0·150–0·276; p<0·0001). The most frequent all-grade adverse events were neutropenia and nausea. 222 (77%) of 287 patients in the ibrutinib group and 212 (74%) of 287 patients in the placebo group reported grade 3–4 events; the most common grade 3–4 adverse events in both groups were neutropenia (154 [54%] in the ibrutinib group vs 145 [51%] in the placebo group) and thrombocytopenia (43 [15%] in each group). A safety profile similar to that previously reported with ibrutinib and bendamustine plus rituximab individually was noted. Interpretation: In patients eligible for bendamustine plus rituximab, the addition of ibrutinib to this regimen results in significant improvements in outcome with no new safety signals identified from the combination and a manageable safety profile. Funding: Janssen Research & Development.